Epidemiological profile of syphilis in pregnant women in the state of Bahia between the years 2015-2021 (Research, Society and Development, 2023)
Introduction: Bahia stands out for being one of the Brazilian states with the highest number of cases of gestational syphilis (GS). Such evidence makes epidemiological studies in the state indispensable, in order to assist in the implementation of more effective public policy measures in the fight against gestational syphilis. Objective: In this context, this investigation seeks to outline the epidemiological profile of GS in the state of Bahia in the period between 2015 and 2021 and to identify the vulnerability profile of GS in the state of Bahia. Methods: This is a cross-sectional, exploratory study, with a quantitative and retrospective approach, with data collected from the Notifiable Diseases Information System (SINAN). Data analysis was performed using the GraphPad Prism program. Results: Syphilis is one of the STIs that most infects pregnant women and has the greatest global impact, in Bahia between 2015-2021 a total of 17,412 confirmed cases of gestational syphilis were reported. A spatial analysis of this distribution shows that Salvador (4,471 cases) and Feira de Santana (1,319 cases) are the municipalities in Bahia with the highest incidence in the period under study. Through the data obtained during the investigation, a greater vulnerability was evidenced in young brown pregnant women with low education and who have informal work as an occupation or are housewives. Conclusion: With the present study, we seek to highlight the endemic nature of GS in the state of Bahia and reinforce the need to adopt effective measures to combat the infection.